2010
DOI: 10.1590/s1415-43662010000800001
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de metais pesados e alterações químicas em Cambissolo cultivado com meloeiro

Abstract: RESUMOCom a utilização intensiva de agroquímicos, os solos cultivados podem ter o teor de metais pesados disponíveis às plantas aumentado com possível contaminação subsequente da cadeia trófica. Propôs-se, no presente trabalho, avaliar a influência do tempo de uso agrícola de um Cambissolo Háplico cultivado com meloeiro (Cucumis melo L.) sob o acúmulo de metais pesados e as características químicas do solo. O solo com plantios de meloeiro com um, dois e três anos de implantação foram avaliados, além de uma áre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Agriculture is one of the most important sources of heavy metal pollution of bodies of water, largely through fertilizers (Cd, Cr, Pb, Zn) and pesticides (Cu, Pb, Mn, Zn) (Mendes et al, 2006, Silva et al, 2016. In this respect, although agrochemicals are a decisive factor in increasing yields, they can also cause heavy metal contamination (Mendes et al, 2010). For example, fertilizers made from phosphate rocks can increase levels of heavy metals such as Cd, Cu, Mn, Ni, Pb and Zn in the soil (Freitas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is one of the most important sources of heavy metal pollution of bodies of water, largely through fertilizers (Cd, Cr, Pb, Zn) and pesticides (Cu, Pb, Mn, Zn) (Mendes et al, 2006, Silva et al, 2016. In this respect, although agrochemicals are a decisive factor in increasing yields, they can also cause heavy metal contamination (Mendes et al, 2010). For example, fertilizers made from phosphate rocks can increase levels of heavy metals such as Cd, Cu, Mn, Ni, Pb and Zn in the soil (Freitas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the 10 and 26 year-old orchards, the Cu contents were also higher than the Cu values found in Oxisols, (surface 2.03 mg kg -1 ) and in the subsurface (3.40 mg kg -1 ). Mendes et al (2010) found a significant increase in the Cu level in soil under melon, with values as high as 102.5 and 125.33 mg kg -1 , above the prevention value of 60 mg kg -1 (CONAMA, 2009).…”
Section: Resultsmentioning
confidence: 90%
“…In the 20-40 cm layer, the contents of Pb varied from UD to 3.47 mg kg -1 in the CA and from UD to 7.88 mg kg -1 in the RA. In contrast, Mendes et al (2010) and others in the RA (Figure 4). The soils contained higher Mn levels in the RA after 6, 11, 14, 16, 17, and 19 years, differing from the areas after 8, 9, 10, and 26 years, where the levels were higher in CA than in RA.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…They observed vermicompost was more efficient in reducing toxicity of Cu to the plants, since Cu is easily complexed with soil organic matter (SOM). High Cu concentrations in soils were also reported in areas with mango (Mangifera indica) trees, cultivated for more than 26 years in Pernambuco State (Silva, Nascimento, Biondi & Cunha, 2012), and with melon (Cucumis melo), cultivated for two years in Rio Grande do Norte State (Mendes, Duda, Nascimento, Lima, & Medeiros, 2010). In both cases, Cu contents were higher than the prevention value (60 mg kg -1 ) allowed by the Brazilian legislation (Conselho Nacional do Meio Ambiente [CONAMA], 2009) for Cu in soils.…”
Section: Introductionmentioning
confidence: 85%